Application of microwave radiation in the synthesis of aspartic acid/lactic acid biodegradable copolymer - Pagacz, J.; Polaczek, J.; Pielichowski, J.; Migdał, M.; Tokarska, A. (Polimery, 2022)
The results of investigations on the new method, based on microwave radiation use, of preparation of aspartic acid (KA)/lactic acid (KM) biodegradable copolymer (PAL) are presented. The syntheses were carried out at various molar ratios of reagents, different temperature and radiation dose, in the solution or bulk, without catalyst (H3PO4) or - for comparison - with it (Table 1-4). The course of degradation of PAL copolymers prepared in bulk, in physiological solutions was also evaluated (Fig. 1). Chemical structure of the products were characterized by infrared spectroscopy (FT-IR) (Fig. 2 and 3) and nuclear magnetic resonance (1H NMR) (Fig. 4). Molecular weights of the products (Table 5) were determined by gel permeation chromatography (GPC). Thermal properties were investigated by thermogravimetry (TG) (Fig. 5, Table 6) and differential scanning calorimetry (DSC) (Fig. 6 and 7, Table 7). Dependently on the method of copolymerization and its conditions the resulted materials varied in molecular weights, crystallinity, solubility and thermal stability.